Smart Waste Management System - Rexsan.S; Tharakan.T; Thivyapranath.B; R.K.Sheron; Shashika.L (International Journal of Engineering and Management Research, 2022)
Waste management is a problem that we are thriving worldwide. Still, a majority of the world is trying to figure out a way to administrate and monitor waste in an efficient way to minimize the outburst of environmental perils. Even though various methodologies and technologies have been used to find a solution still none of them has reached their full potential level. This paper proposes an approach to provide a solution for waste management at its starting point with cost-effective benefits and a higher rate of practicality. With the help of the Internet of things (IoT) and Machine Learning (ML) based Image processing we have developed a handheld device with an integrated app to find a solution for this problem. The device will have the application to monitor the bin's environment sending data to the admin to make further actions if necessary, regarding the maintenance of the bin. Furthermore, the bin will be able to communicate with the user when requested. To make the user more involved in using the bin properly the app will provide a rewarding system to encourage the user to keep using the bin properly. With the joined eco-system of all these technologies, waste management and segregation can be done more effectively with less manpower and more awareness and encouragement among the users creating a new era of a clean eco-system.